2008
DOI: 10.1371/journal.pone.0004064
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 Autoubiquitination-Independent Activation of the NFκB and MAPK Pathways in Response to IL-1 and RANKL

Abstract: The adapter protein TRAF6 is critical for mediating signal transduction from members of the IL-1R/TLR and TNFR superfamilies. The TRAF6 RING finger domain functions as an ubiquitin E3 ligase capable of generating non-degradative K63-linked ubiquitin chains. It is believed that these chains serve as docking sites for formation of signaling complexes, and that K63-linked autoubiquitination of TRAF6 is essential for formation and activation of a complex involving the kinase TAK1 and its adapters, TAB1 and TAB2. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
178
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(187 citation statements)
references
References 43 publications
8
178
0
1
Order By: Relevance
“…In support of this notion, recent evidence points to the paradigm that TRAF6-mediated ubiquitination is an important step for the formation and activation of a signaling complex that includes UBC13, TAK1, and its adaptors TAB1 and TAB2 (40,(45)(46)(47)(48). In a more recent study, Walsh et al, (42) showed that the RING finger of TRAF6 is required for the activation of TAK1, and TRAF6 was found to interact with TAK1. Most importantly, TRAF6 was found to induce ubiquitination of NEMO, which in turn contributes to TRAF6-mediated activation of NF-B.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In support of this notion, recent evidence points to the paradigm that TRAF6-mediated ubiquitination is an important step for the formation and activation of a signaling complex that includes UBC13, TAK1, and its adaptors TAB1 and TAB2 (40,(45)(46)(47)(48). In a more recent study, Walsh et al, (42) showed that the RING finger of TRAF6 is required for the activation of TAK1, and TRAF6 was found to interact with TAK1. Most importantly, TRAF6 was found to induce ubiquitination of NEMO, which in turn contributes to TRAF6-mediated activation of NF-B.…”
Section: Discussionmentioning
confidence: 94%
“…TRAF6 is a well characterized E3 RING ligase involved in Toll-like receptor, RANK, and IL-1R signaling transduction pathways. More importantly, it has been shown recently that TRAF6 undergoes auto-ubiquitination and promotes K63-linked ubiquitination of target proteins (40,42). Thus, we probed the involvement of TRAF6 in the PMMAinduced ubiquitination events of NEMO.…”
Section: Pmma Particles Activation Of Nf-b and Map Kinase Pathways Rementioning
confidence: 94%
“…TRAF6, as an E3 ligase, could promote the synthesis of unanchored polyubiquitin chains, which activate the IKK complex (37). Lysine-deficient TRAF6 has been shown to activate the NF-kB and MAPK pathways in response to IL-1 and RANKL (38). Wang et al (39) reported that transubiquitination induced by two TRAF6 muteins is insufficient for NF-kB activation.…”
Section: Discussionmentioning
confidence: 99%
“…8a) in LRRC19 and TRAF2 or TRAF6 co-expressing HEK293T cells. As TRAF6 and TRAF2 could be ubiquitinated in the process of signal transduction [26][27][28] , we hypothesized that the interaction of LRRC19 and TRAF6 or TRAF2 could affect the ubiquitination of TRAF6 and TRAF2. While the cells were transfected using Myc-tagged TRAF2 with control empty plasmid, degradation of TRAF2 could be observed (Fig.…”
Section: Lrrc19 Promotes Expression Of Antimicrobial Substancesmentioning
confidence: 99%